THE MEDIATING EFFECT OF SCHOOL-BASED MANAGEMENT ON SCHOOL CLIMATE, BUREAUCRACY AND EFFECTIVENESS IN SECONDARY SCHOOL - Yusuf, Habibat Abubakar; Amzat, Ismail Hussein; Saidin, Khaliza (2019)
School effectiveness is a global issue among education stakeholders particularly in developing countries where difficulties in delivering quality education is widespread. However, internal and external factors in schools make school outcomes unpredictable, thus making bureaucracy an effective managerial and analytical tool which can be used to examine and direct organizational structure. This study examined the mediating effect of school-based management on school climate, bureaucracy and effectiveness in secondary schools. A quantitative research of cross-sectional survey with population of 7,533 teachers was employed. Four sets of instruments were adapted and administered on sample of 350 teachers in Nigeria secondary schools through stratified random sampling of the proportionate method. Structural Equation Modelling (SEM) analysis was employed to test the fitness of data in relation to constructs in the model and further confirm hypotheses generated for this study. The findings of revealed that underlying predictors were true measure of their respective constructs. There is a mediation effect of school-based management on bureaucracy and school effectiveness while other path analysis revealed that school-based management did not mediate between school climate and school effectiveness. This study expands theory on bureaucracy as bright side and validates the assertion that, bureaucracy is required in public schools.